Communicative Types Of Self-Disclosure In Public Speaking Setting - Kyrychuk, Larysa (Lesya Ukrainka Eastern European National University, 2017)
The present paper focuses on the study of the communicative nature of selfdisclosure as a technique of verbal influence on people. The phenomenon of self-disclosure is interpreted as the process of divulging private information to others. The aim of the study is to determine the specific features of self-disclosure in a public speaking context. The paper discusses the communicative conventions and parameters of the public speaking scenario as the factors that determine a certain manner of self-disclosing. The key assumption of the study is that public selfdisclosure should be viewed as a tactic of self-presentation that promotes the speaker’s image building. In order to indicate the verbal forms that speakers use while disclosing private information in public the discourse and lexical-grammatical analyses of eight celebrity interview texts are conducted. The results of the research demonstrate that the speakers use recurrently certain verbal patterns which are identified as statements of self-description (it includes statements of self-confirmation, self-assurance, personal preferences and personal aspirations), self-narrative and attitude statements. The study also shows which types of the statements are used more frequently than the others, particularly, the statements of self-confirmation, personal aspirations and self-narratives are apparently preferred by the speakers as tactics of public se lf-disclosure. The paper highlights the fact that the self-disclosure tactics are employed by public speakers selectively and that their choice is motivated by the speakers’ strategic goal of impression management. Статтю присвячено вивченню комунікативної природи саморозкриття як методу вербального впливу на людей. Явище само-розкриття визначається як процес розголошення приватної інформації про себе. Мета дослідження – визначити специфіку саморозкриття у ситуації публічного мовлення. У статті проаналізовано умови й параметри сценарію публічного мовлення як чинники, що зумовлюють певну манеру саморозкриття. Базовою позицією дослідження є трактування само-розкриття як тактики самопрезентації, що сприяє створенню іміджу мовця. Для визначення вербальних форм, які використовують мовці, розголошуючи приватну інформацію про себе, було здійснено дискурсивний та лексико-граматичний аналіз 8 текстів інтерв’ю зі знаменитостями. Результати дослідження засвідчили те, що мовці постійно використовують певні вербальні моделі, які визначаються як висловлювання автохарактеризації (до цієї групи належать висловлювання самоствердження, самопереконання, особистих уподобань та особистих прагнень), автонаративу та висловлювання особистої позиції. Дослідження також продемонструвало, які саме типи висловлювань використовують частіше, ніж інші, зокрема, висловлюванням само-ствердження, особистих прагнень та автонаративу як тактикам саморозкриття надається очевидна перевага. Стаття акцентує вибірковість застосовування мовцем тактики саморозкриття, оскільки їх вибір є мотивованим стратегічною метою мовця здійснювати контроль за створенням враження.
Keywords: self-disclosure; self-presentation; public speaking; communicative tactic; private information; verbal pattern; саморозкриття; самопрезентація; публічне мовлення; комунікативна тактика; приватна інформація; вербальна модель